Facile synthesis of ZnO nanoparticles for the effective photodegradation of malachite green dye in aqueous solution - Meena, Parmeshwar Lal; Poswal, Krishna; Surela, Ajay Kumar (Water and environment journal : WEJ, 2022)
Zinc oxide (ZnO) nanoparticles were synthesized using a simple co‐precipitation method and applied for effective photodegradation of malachite green (MG) dye in an aqueous solution. The synthesized ZnO nanoparticles were characterized by X‐ray diffraction (XRD), field emission scanning electron microscopy (FESEM), energy dispersive spectroscopy (EDS), Fourier transform infrared (FTIR), and ultraviolet–visible (UV–vis) spectroscopic techniques. XRD pattern is confirmed the formation of crystalline ZnO nanoparticles with hexagonal wurtzite structure while the FESEM image validates the preparation of disc‐like spherical nanostructures agglomerated with the size of 30–50 nm. The nanostructures exhibited a strong UV absorption band at 370 nm, and the bandgap energy calculated from the Tauc plot is 3.12 eV. The prepared ZnO nanoparticles exhibited 92.07% photodegradation efficiency against the MG dye in 2 h of UV light irradiation at pH 8. The experimental data has followed the pseudo‐first‐order kinetic model, and the rate constant value obtained is 20.433 × 10−3 min−1. Thus, the synthesized ZnO nanoparticles degraded MG dye effectively and can be utilized for environmental remediation purposes.